Trends in acarology : proceedings of the 12th International Congress - Sabelis, M. W.; Bruin, J. (Springer, 2010)
"Acari are everywhere and acarologists go after them - some aiming to explore the bewildering diversity of the mites and ticks, others trying to understand the how and why of their being. For the past 50 years, the International Congress of Acarology has been the foremost forum for worldwide communication on the knowledge of mites and ticks, helping researchers and students to look beyond the borders of their disciplines. Many mites and ticks have economic consequences as they are pests of agricultural, veterinary and medical importance, and several species have become model organisms for studies in modern biology. The 96 contributions to Trends in Acarology - reflecting a vast variety of disciplines, such as molecular biology, biochemistry, physiology, microbiology, pathology, ecology, evolutionary biology, systematic biology, soil biology, plant protection, pest control and epidemiology - have all been reviewed and carefully edited. The resulting voIume contains a wealth of new information, that may stimulate research for many years to come."--Back cover.